THE ROLE AND SIGNIFICANCE OF MODERN BANKS - Eshqulov Baxodir Karimberdi o‘g‘li (Web of Journals Publishing, 2025)
This article expands on role of modern banks in economy, basic functions, types and development of digital banking services. The role of banks in lending, working with deposits, providing investment services is substantiated by examples and facts. Also, through the opinions of industry scientists, the importance of banks in society is revealed.